2022
DOI: 10.23736/s0390-5616.21.05344-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the frontal aslant tract and surgical perspectives

Abstract: The frontal aslant tract (FAT) is an intralobar white matter fasciculus providing dense connections between the medial part of the superior frontal gyrus, in particular the pre-supplementary motor area (SMA) and the SMA proper, and the lateral part of the frontal lobe, especially the inferior frontal gyrus. Although this tract has been characterized belatedly, it has received important attention in recent years due notably to its increasingly evidenced role in the speech and language networks. As cerebral tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Disconnection analyses revealed that lower scores in phonemic fluency were related to left FAT and IFOF partial damage/disconnection, specifically in its frontal part. The left FAT plays a pivotal role in speech production and initiation ( Chernoff et al, 2019 , Dragoy et al, 2020 , Kemerdere et al, 2016 , Kinoshita et al, 2015 ), and implications in working memory and executive functions (in particular, inhibition) have been reported (see Burkhardt et al, 2021 , for a review). Interestingly, these last cognitive processes are also involved in lexical retrieval on phonemic cue ( Robinson et al, 2012 , Shao et al, 2014 , Troyer et al, 1997 , Unsworth et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Disconnection analyses revealed that lower scores in phonemic fluency were related to left FAT and IFOF partial damage/disconnection, specifically in its frontal part. The left FAT plays a pivotal role in speech production and initiation ( Chernoff et al, 2019 , Dragoy et al, 2020 , Kemerdere et al, 2016 , Kinoshita et al, 2015 ), and implications in working memory and executive functions (in particular, inhibition) have been reported (see Burkhardt et al, 2021 , for a review). Interestingly, these last cognitive processes are also involved in lexical retrieval on phonemic cue ( Robinson et al, 2012 , Shao et al, 2014 , Troyer et al, 1997 , Unsworth et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the FAT in verbal fluency on phonemic cue is in line with previous results ( Catani et al, 2013 ) on neurodegenerative diseases. Moreover, superior cortical terminations of this tract are found in the Supplementary Motor Area (SMA and preSMA) ( Burkhardt et al, 2021 , Catani et al, 2013 ): a lesion in this part of the superior frontal gyrus, anterior to the precentral gyrus, may lead to the so-called SMA syndrome, implying transient akinesia, mutism and dysexecutive deficits ( Bannur and Rajshekhar, 2000 , Sjöberg et al, 2019 , Vergani et al, 2014 ). At the same time, the SMA is connected by the FAT to the inferior frontal gyrus, in particular to Broca’s area ( pars opercularis and pars triangularis ) ( Burkhardt et al, 2021 , Catani et al, 2013 ), which is involved in speech articulation and phonemic fluency ( Birn et al, 2010 , Cattaneo et al, 2011 , Heim et al, 2008 , Sarubbo et al, 2020 , Zacà et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One recently described tract is the frontal aslant tract (FAT), which runs from the supplementary motor area to the pars opercularis of the inferior frontal gyrus (IFGOp) ( Catani et al, 2013 , Thiebaut de Schotten et al, 2012 ). Since its initial description, research into the structure and function of the FAT has greatly expanded the current understanding of the tract, contributing not only to the neurocognitive understanding of the tract but also to its consideration in a clinical context ( Burkhardt et al, 2021 , La Corte et al, 2021 ). One area that the FAT has been commonly associated with includes both motor speech disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%